The exclusive presence of the chronic pulmonary disease could be more important in affecting autonomic cardiac modulation than the severity of airflow obstruction: Analysis using heart rate variability. (April 2018) - Ricci-Vitor, Ana Laura; Marques Vanderlei, Luiz Carlos; dos Santos, Ana Alice Soares; Vanzella, Lais Manata; Destro Christofaro, Diego Giulliano; de Abreu, Luiz Carlos; Cipulo Ramos, Ercy Mara; de Godoy, Moacir Fernandes; Filho, Celso Ferreira; Ferreira, Celso
Abstract: The autonomic nervous system regulates the caliber of the airways, blood flow, secretion production, modulates the inflammatory response and modulates airway responses to inflammation. Despite this, some intrinsic features could be more important in affecting autonomic modulation than the airflow severity. This study aimed to analyze the effects of chronic obstructive pulmonary disease (COPD) on autonomic modulation through heart rate variability (HRV) and its relationship with airflow severity. Outpatients with COPD (n = 30) and a control group (n = 26) were evaluated. The main outcome measures were anthropometry, spirometry and HRV. The presence of COPD had a large effect on autonomic modulation, demonstrated by a significant reduction in 6 out of 12 HRV indices according to the comparisons between the COPD groups (high and low severity) and the control group through HRV indices (rMSSD: 13.5 ± 7.3 vs. 10.4 ± 6.3 vs. 20.7 ± 7.1 ms; SDNN: 22.0 ± 11.2 vs. 17.1 ± 8.0 vs. 33.6 ± 13.8 ms; SD1: 9.6 ± 5.2 vs. 7.4 ± 4.5 vs. 14.6 ± 5.0 ms; SD2: 29.5 ± 15.2 vs. 22.9 ± 10.7 vs. 44.8 ± 20.0 ms). However, the severity of COPD presented no significant differences even when considering age, sex and body mass index (BMI). This study suggests that the presence of COPD could be more important in affecting HRV than the severity of airflow obstruction, independent of the sex, age or BMI.